COMPARATIVE ANALYSIS OF GENOME-WIDE VARIANTS IN ANKAMALI PIGS OF KERALA WITH EXOTIC PIG BREEDS - Manoj, M (The Indian Journal of Animal Sciences, 2026)
The Ankamali pig is a domesticated indigenous variety from Kerala. Conservation of such native pig varieties is vital for future animal production due to their potential as sources of genetic diversity. Present study was undertaken with the objective of identifying genome-wide genetic variants in Ankamali pigs using next generation sequencing (NGS) technology and their genome-wide comparison with exotic pig breeds. Genomic DNA was extracted from 12 pigs, pooled after quality checks and subjected to whole genome sequencing (WGS). The sequencing produced 1.36 billion quality-checked reads, with 1.357 billion successfully mapped to the reference genome. Variant calling analysis revealed 26.6 million single nucleotide variants, including 21.3 million single nucleotide polymorphisms and 5.3 million indels. Annotation of these SNVs in the Ankamali pig genome revealed that 45.09% of variants were located in intronic regions, while 37.79% variants were present in intergenic regions. When comparing Ankamali pigs to Duroc pigs, fewer SNPs were found in the Duroc breed. A noticeable difference in the number of variants were found between Ankamali pigs and the Danish Large White pig. Whole genome comparisons among Ankamali pigs, Wannan Black pigs, and Anquing Six-End White pigs with the Sus scrofa reference genome 11.1 showed comparable total numbers of SNVs. The proportion of variants detected in intronic, upstream, downstream and 5′UTR region were different in Ankamali pigs, Wannan black and Anquing six-end white pig. The higher genomic variability in Ankamali pigs compared to the reference genome highlights their unique phenotypic and genetic traits, underscoring the importance of conservation efforts.